Mesoporous silica-based hybrid materials for bone-specific drug delivery. Issue 8 (18th July 2019) - Pasqua, Luigi; De Napoli, Ilaria Ester; De Santo, Marzia; Greco, Marianna; Catizzone, Enrico; Lombardo, Domenico; Montera, Gabriella; Comandè, Alessandra; Nigro, Alessandra; Morelli, Catia; Leggio, Antonella
Abstract : A mesoporous silica-based drug delivery device potentially useful for bone-specific drug delivery has been designed, developed and characterized starting from MSU-type mesoporous silica. Abstract : A mesoporous silica-based drug delivery device potentially useful for bone-specific drug delivery has been designed, developed and characterized starting from MSU-type mesoporous silica. The proposed system consists of a mesoporous silica nanoparticles (MSN) based vehicle, presenting alendronate as a targeting functionality for bone tissue while ibuprofen is used as a model molecule for the drugs to be delivered. The particles are functionalized on the external surface using a propionitrile derivative that is successively hydrolyzed to a carboxylic group. Alendronate, one of the most used member of the diphosphonate drug class, is electrostatically bonded to the external carboxyl functionalities of mesoporous silica. The obtained material has been characterized by powder X-ray diffraction, N2 adsorption–desorption porosimetry, UV-vis spectrophotometry, FT-IR spectrometry and MAS-NMR 13 C and 29 Si. Hydroxyapatite, which simulates the bone matrix, has been synthesized with the aim of testing the targeting activity of the obtained device. In a separate test, the MSNs have been loaded with ibuprofen, a non-steroidal anti-inflammatory drug (NSAID), and its release has been determined under neutral conditions by HPLC. Moreover, biological tests were carried out. The tested devices did not show any toxicity towards normal cells, confirming their high biocompatibility and the lack of off-target effects.